Peran Guru Dan Orang Tua Dalam Melaksanakan Pendidikan Inklusi Untuk ABK (Anak Berkebutuhan Khusus) Di Sekolah - Dona Liza; Leni Marlina; Iqbal Geni Pratama; Opi Andriani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
The aim of this research is to determine the role of teachers and parents in implementing education for children with special needs (children with special needs) at school. This research uses a qualitative descriptive research method. Data collection techniques include: observation and interviews. The research subjects or informants were the school principal, class teacher/homeroom teacher and student parents. Collaboration between parents and teachers is very necessary in the formation and improvement of inclusive education. The research results show that: (1) In inclusive education, the role of the principal as the highest decision holder in an institution greatly influences the direction and goals to be achieved by the institution. (2) There are many factors inhibiting the management of inclusive education at SDN Talang Pantai from the beginning of management until now. The role of the teacher/class teacher is very important in learning, namely the teacher always provides motivation when starting the teaching and learning process, the teacher always pays more attention to children with special needs compared to other normal children and the teacher/class teacher always guides children with special needs when carrying out ongoing learning. (3) Efforts made by parents towards children with special needs, namely that parents pay attention to the child, provide appropriate guidance when implementing inclusive education at school. Parents of children with special needs need to be directly involved in making every decision, starting from school placement to the collaboration they carry out with the school.